2020
DOI: 10.1186/s13018-020-01624-7
|View full text |Cite
|
Sign up to set email alerts
|

Is hip fracture surgery safe for patients on antiplatelet drugs and is it necessary to delay surgery? A systematic review and meta-analysis

Abstract: Background: Hip fractures are common and account for a large proportion of orthopedic surgical admissions in elderly patients. However, determining the timing for surgery has been controversial for patients who develop hip fractures while on antiplatelet treatment. Methods: Computerized databases for studies published from the inception date to January 2020, including the Cochrane Library, PubMed (Medline), EMBASE, Web of Science TM , ClinicalTrials, ClinicalKey, and Google Scholar, were searched using the key… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 62 publications
0
27
0
Order By: Relevance
“…In addition, the role of anti-inflammatory or antiplatelet drugs in blood management cannot be ignored. Recent meta-analyses showed that early hip fracture surgery was significantly related to a higher transfusion rate in patients with antiplatelet treatment than patients without antiplatelet treatment [27]. Therefore, antiplatelet drugs may play a role in influencing blood administration for TKA patients, and we will further study this potential mechanism in a later study.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, the role of anti-inflammatory or antiplatelet drugs in blood management cannot be ignored. Recent meta-analyses showed that early hip fracture surgery was significantly related to a higher transfusion rate in patients with antiplatelet treatment than patients without antiplatelet treatment [27]. Therefore, antiplatelet drugs may play a role in influencing blood administration for TKA patients, and we will further study this potential mechanism in a later study.…”
Section: Discussionmentioning
confidence: 92%
“…showed a small increase in bleeding, as evidence by transfusion rates (OR=1.21; 95%CI: 1.01 to 1.44; p < 0.05) and haemoglobin drop (WMD=0.75; 95%CI, 0.50 to 1 g/dL; p < 0.001) [130]. Patients treated with clopidogrel with a surgical delay of 5 days or more had more complications (pulmonary embolism, myocardial infarction, heart failure and pressure ulcers), than those that were treated in 24-72 h [130]. Although interruption of antiplatelet therapy in those at low risk for thrombotic complications may be considered, it seems safer to continue antiplatelet therapy in patients with a high thrombotic risk.…”
Section: Antiplatelet Agentsmentioning
confidence: 92%
“…Current evidence from meta-analyses of observational studies including 245 patients treated with clopidogrel compared with 2400 controls indicates that it is unnecessary to delay surgery to restore platelet function when patients with hip fractures receive aspirin alone, clopidogrel alone or clopidogrel combined with aspirin. Furthermore, early surgery (≤48 h) significantly reduced mortality (OR=0.43; 95%CI: 0.23 to 0.79; p=0.006) and hospital stay (WMD = -6.05; 95%CI: -7.06 to -5.04; p < 0.001), which is important for patient recovery [130,131].…”
Section: Antiplatelet Agentsmentioning
confidence: 96%
See 1 more Smart Citation
“…Since all available antiplatelet agents (i.e., aspirin, clopidogrel, ticagrelor and ticlopidine) act as irreversible inhibitors of platelet aggregation, the reversal of their effect mainly depends upon platelet half-life which varies between 7 and 10 days [62]. Many studies have shown that, even exposed to further potential blood loss, subjects taking antiplatelet agents do not experience more major bleeding events or mortality and do not require more blood transfusions [63][64][65][66]. Conversely, any delay with surgery is associated with poorer outcomes [64][65][66][67].…”
Section: Management Of Antiplatelet Therapymentioning
confidence: 99%